2016
DOI: 10.1002/14651858.cd010227.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate monotherapy and methotrexate combination therapy with traditional and biologic disease modifying anti-rheumatic drugs for rheumatoid arthritis: A network meta-analysis

Abstract: Methotrexate monotherapy and methotrexate combination therapy with traditional and biologic disease modifying antirheumatic drugs for rheumatoid arthritis: A network meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 211 publications
1
76
1
3
Order By: Relevance
“…We elected to include only trials in which, in 1 arm, bDMARD/tofacitinib was administered with methotrexate, because this combination reflects the most frequent clinical practice and was felt to provide an adequate sample of the majority of RCTs of advanced therapy. This decision also allowed us to leverage a completed systematic review and network meta‐analysis to identify articles (see literature search below) . We purposely included few other restrictions in our eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We elected to include only trials in which, in 1 arm, bDMARD/tofacitinib was administered with methotrexate, because this combination reflects the most frequent clinical practice and was felt to provide an adequate sample of the majority of RCTs of advanced therapy. This decision also allowed us to leverage a completed systematic review and network meta‐analysis to identify articles (see literature search below) . We purposely included few other restrictions in our eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Trials were identified from a systematic literature search that had been previously conducted for a network meta‐analysis of methotrexate‐based DMARD treatments . This search was comprehensive up until January 2016 of 9,817 records identified from published databases (Medline, Embase, and Cochrane Central), supplemented with hand searches of Cochrane reviews and meeting abstracts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…New treatment strategies for RA, including early and effective DMARDs, have resulted in reduced disease activity, but the optimal treatment of lung involvement is still a dilemma [81]. So far, no randomized controlled trials in RA-ILD have been conducted.…”
Section: Treatmentmentioning
confidence: 99%